Situation Report: Romania, 15 October 1987 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Changes in the Nomenklatura / by Paul Gafton Officials in Charge of Energy Dismissed / by Paul Gafton Some Diplomats Removed / by Paul Gafton Reorganizations and Reshuffle / by Paul Gafton Developments in China as Seen from Bucharest / by Crisula Stefanescu Soviet Press Continues Reporting on Bleak Conditions in Romania / by Vladimir Socor The Orthodox Church and the State: A Change in Attitude? / by Dan Ionescu Proposals for Reform and Appeals to Gorbachev from Romanian Dissidents / by Vladimir Socor